Challenges of Sustainable Development of Education In Georgia - Molashvili, Gvantsa (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Georgia has signed an Association Agreement with the European Union, which aims to increase the country's engagement in EU-developed strategies and programs. Access to quality education is a prerequisite for achieving sustainable development. To fulfill its objectives, modernizing the education system and equipping young people with 21st-century skills are necessary. These skills include critical thinking, problem-solving, creativity, emotional intelligence, social and collaborative abilities, digital skills, and more. Research shows that in Georgia, students' academic performance and access to quality education remain challenges. Students demonstrate weak analytical, social, and logical skills. Research also indicates that they lack awareness of their responsibilities and roles in achieving sustainable development goals. Additionally, teachers are not adequately prepared to face new challenges; retraining is needed so they can keep up with the rapidly changing environment around them. The article discusses several factors that hinder the achievement of sustainable development goals in education. It highlights that the education sector still faces many challenges, including inclusivity issues, infrastructural problems, a lack of adequately competent teachers in sustainable development, and the need for curriculum modernization.